The Implementation of Pregnant Mother Class Program in Aceh Barat District - Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitriani Fitriani (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2018)
The total of pregnant women in Aceh Barat District in 2018 is 4453 0 people. The total of deaths was 3 and than the total of infant deaths was 90. The importance of pregnant mothers class programs as an effort to reduce maternal mortality and infant mortality rates. The purpose of this study was to analyze the study of Communication, Resources, Disposition, and Bureaucratic Structure in the Implementation of the Mother Class Program in West Aceh District. This type of research is descriptive qualitative research that is the method used to explore or analyze a study but is not used to make broader conclusions. The sampling technique used purposive sampling with 16 main informants, 1 key informant and 1 supporting informant. Data collection techniques with in-depth interviews. Data analysis uses content analysis. The results of research on communication studies are still not good, resources are incomplete. Disposition is still lacking in commitment, and bureaucratic structure is still lacking in cooperation. The implementation of the Pregnant Women Class Program in West Aceh district is still inappropriate and there are still many obstacles and obstacles. The conclusion is that there is still a lack of communication across sectors, the lack of resources to carry out maximum implementation, the lack of commitment from decision makers, and the bureaucratic structure is still lacking of cooperation so that the implementation of the pregnant mothers class program cannot run properly and optimally. Suggestions are expected to build good communication across sectors, decision makers seek to maximize available resources in the implementation of classes for pregnant women, build cooperation in bureaucratic structures and for pregnant women are expected to continue to follow the Pregnant Women Class routinely and to the end so that pregnant women class programs can run effectively.